Thermal and Thermo-hydraulic Performance of Packed Bed Solar Air Heater - Hans, V. S.; Singh, Sukhmeet; Gill, R. S. (Journal of Agricultural Engineering, 2014)
Modification of flow passage of air in a solar air heater using a packing material is one of available techniques to considerably improve thermal performance of solar air heaters. In an outdoor experimental study, thermal and thermohydraulic performance of a packed bed solar air heater were evaluated and compared with that of a conventional solar air heater. It was observed that due to presence of mild steel chips in the flow passage of air in packed bed solar air heater, its thermal efficiency improved considerably as compared to that of conventional solar air heater for the entire range of Reynolds number considered in the investigation. Thermo-hydraulic performance of packed bed solar air heater was found to be better than that of conventional solar air heater for most of the Reynolds number range considered. However, beyond Reynolds number of 15000, conventional solar air heater outperformed packed bed solar air heater in terms of effective efficiency.